PERAN GCG DAN STRUKTUR KEPEMILIKAN DALAM MENDETEKSI MANAJEMEN LABA MELALUI DISCRETIONARY REVENUE - Marinus Gea (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2017)
This study aims to examine the role of good corporate governance (GCG) and the ownership structure in the control of management incentives to perform earnings management. GCG in this study measured using indices issued by GCG agencies in Indonesia, Indonesian Institute for Corporate Directorship (IICD). Ownership structure under test consists of managerial ownership, institutional ownership, and foreign ownership. Earnings management measured by discretionary revenue models of Stuben (2010). Samples were analyzed are a manufacturing company study period of 2009 to 2012. Testing the hypothesis is done by using multiple linear regression method. The test results showed that the GCG proven to reduce earnings management. However, all of the ownership structure in this study is not proven negative effect on earnings management. Implications of this research are expected to contribute as additional information for practitioners, academics and policy makers related to the implementation of good corporate governance and ownership structure and its impact on earnings management incentive measures